MANIFESTASI YANG TRANSENDEN DALAM AYAT KURSI - Abdul Muaz; Muhamad Khozinul Huda; Tri Budi Prasetyo (An-Nufus, 2020)
This article examines the name of God in Ayat Kursi (QS. Al-Baqarah (2): 255) from the perspective of a Sufistic interpretation. Discussing this paper will emphasize the interpretation of the name Allah Swt. and His manifestations mentioned in the verse. To analyze this topic, the author uses a literature review analysis approach from both the main and relevant sources. A number of questions to facilitate writing this paper include: Why is Ayat Kursi interesting for discussing divine themes? Does the content in the Ayat Kursi reveal the concept of divinity? Is there a divine name that is mentioned specifically and places a higher priority than other names of His in the verse? Is there any relevance of Ayat Kursi for the present context? Some of the findings that the author can conclude from dissecting this issue include: The Ayat Kursi is an existentially "complete package"; there is the word Allah as an essential affirmation accompanied by the phrase tauhid (laa ilaha illa Huwa), there is the word al-Hayyu as the greatest manifestation of His being followed by the name al-Qayyum, there is an explanation and affirmation from God himself about himself who is transcendently involved immanent in all his creations.